GAME TRANSLATION AND SATISFACTION OF THE PLAYERS: A STUDY ON VIETNAMESE TRANSLATION OF DOTA 2’S HEROES’ SKILL DESCRIPTIONS = DỊCH TRÒ CHƠI VÀ Ý KIẾN NGƯỜI CHƠI: NGHIÊN CỨU BẢN DỊCH VIỆT HÓA PHẦN MIÊU TẢ KỸ NĂNG NHÂN VẬT TRONG DOTA 2 - Nguyễn, Tất Đạt (2020)
Technology has been changing our lives everyday, especially our entertainment activities. Gaming (computer gaming, console gaming, video gaming, mobile gaming etc.) is one of the most popular forms of entertainment, which attracts millions of people around the globe. However, in terms of academic research, there is little attention paid to the field of games in general and game localization in particular. To fulfill such knowledge, this research aims at game translation and the satisfaction of players towards game translation. In order to achieve that target, a thorough study has been carried out upon a Vietnamese translation of a game called Dota 2 while an online survey has helped to collect the opinions from Vietnamese Dota 2 Community on the current translation. Detailed explanation on questionnaire design and data collection was presented in Chapter 3 while the results and discussion are illustrated in Chapter 4. In general, Vietnamese players are unanimous over the standard quality of Dota 2 translation with some specific translation procedures applied by the translator. Despite many limitations due to the scale of this study, it still sheds light on some definitions within the field of game translation. At the end of this research, several suggestions for further studies are also listed for whoever may look into game translation theory in the future.